Integrative analysis of RNA-sequencing and microarray for the identification of adverse effects of UVB exposure on human skin - Yujin Jang; Hye-Won Na; Dong Yeop Shin; Jun Lee; Jun Pyo Han; Hyun Soo Kim; Hyun Soo Kim; Su Ji Kim; Eun-Jeong Choi; Charles Lee; Yong Deog Hong; Hyoung-June Kim; et al. (Frontiers in Public Health, 2024)
BackgroundUltraviolet B (UVB) from sunlight represents a major environmental factor that causes toxic effects resulting in structural and functional cutaneous abnormalities in most living organisms. Although numerous studies have indicated the biological mechanisms linking UVB exposure and cutaneous manifestations, they have typically originated from a single study performed under limited conditions.MethodsWe accessed all publicly accessible expression data of various skin cell types exposed to UVB, including skin biopsies, keratinocytes, and fibroblasts. We performed biological network analysis to identify the molecular mechanisms and identify genetic biomarkers.ResultsWe interpreted the inflammatory response and carcinogenesis as major UVB-induced signaling alternations and identified three candidate biomarkers (IL1B, CCL2, and LIF). Moreover, we confirmed that these three biomarkers contribute to the survival probability of patients with cutaneous melanoma, the most aggressive and lethal form of skin cancer.ConclusionOur findings will aid the understanding of UVB-induced cutaneous toxicity and the accompanying molecular mechanisms. In addition, the three candidate biomarkers that change molecular signals due to UVB exposure of skin might be related to the survival rate of patients with cutaneous melanoma.